Muscle strengthening and prophylactic methods for lower limbs in soccer athletes to minimize muscle imbalance (International Seven Journal of Multidisciplinary, 2023)
In soccer, physical preparation and muscle strengthening are of paramount importance to maximize theperformance of athletes, but physical trainers, when systematizing and planning training, end upoverestimating the anterior thigh muscles and underestimating the posterior thigh muscles, which areimportant. to improve the overall performance of the athlete. Thus, this study aimed to present strengtheningand prevention methods to avoid muscle imbalance in soccer players. For the composition of this research,scientific articles published between the years 1994 to the most current 2023 were consulted. Injuriesresulting from soccer are related to inadequate training, alterations that overload some body structures,causing muscle weakness, which may affect tendons and joints. Muscle strengthening and preventionInternational Seven Multidisciplinary Journal, São José dos Pinhais, v.2, n.2, p. 165-175, mar./apr., 2023methods are important factors to maintain constant muscle balance during training and games, contributingto injury prevention and increasing the level of competitiveness in this sport. DOI:https://doi.org/10.56238/isevmjv2n2-002